Remodeling of Displaced Condylar Fractures with Functional Treatment: High-Quality Radiographic Documentation in Three-Patient Series. Issue 4 (December 2015) - Yildirim, Yavuz; Keller, Eugene E.
Treatment of condylar fractures is variable and controversial. Treatment options for management of condylar fractures include surgical and nonsurgical methods, and if a nonsurgical method is as effective as a surgical method, the former is preferred. Although plain film radiographs and functional outcomes attained through nonsurgical treatment are well established in literature, evidence of the remodeling process through detailed, high-quality imaging is lacking. The purpose of this case series is to describe and illustrate two adults and one pediatric patient with significantly displaced condylar fractures treated nonsurgically with excellent clinical results. It is unique for such patients to have pre- and posttreatment computed tomography scans with high-quality three-dimensional reconstruction as in the case of two adults and to have 3.5-year posttrauma radiographs and 14.5-year follow-up as in the case of the pediatric patient. As such, this report is useful in visually presenting three examples of repositioning and reformation of the temporomandibular joint structures in displaced condylar fractures in a postmenarche 14-year-old female patient, a 21-year-old male patient, and an 18-month-old male patient.